2021
DOI: 10.3389/fonc.2021.705888
|View full text |Cite
|
Sign up to set email alerts
|

Decreased IL-6 and NK Cells in Early-Stage Lung Adenocarcinoma Presenting as Ground-Glass Opacity

Abstract: BackgroundLung ground-glass opacities (GGOs) are an early manifestation of lung adenocarcinoma. It is of great value to study the changes in the immune microenvironment of GGO to elucidate the occurrence and evolution of early lung adenocarcinoma. Although the changes of IL-6 and NK cells in lung adenocarcinoma have caught global attention, we have little appreciation for how IL-6 and NK cells in the lung GGO affect the progression of early lung adenocarcinoma.MethodsWe analyzed the RNA sequencing data of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Another study also found a trend of decreasing numbers and functions of NK cells in nLung, GGNs and SNs 25 . Zhang et al found that this change in NK cells was synchronized with IL‐6 by scRNA‐seq of nLung and GGNs, and further in vitro induced culture revealed that IL‐6 did have a promotional effect on the proliferation of NK cells, and this effect was particularly evident in GGNs 38 . The role of combined cytokine supplementation therapies based on NK cells in NSCLC has recently been demonstrated, and approaches such as NK‐92 and chimeric antigen receptor (CAR)‐transduced NK cells are being explored in lung cancer 39 .…”
Section: Lymphoid Cellsmentioning
confidence: 89%
See 2 more Smart Citations
“…Another study also found a trend of decreasing numbers and functions of NK cells in nLung, GGNs and SNs 25 . Zhang et al found that this change in NK cells was synchronized with IL‐6 by scRNA‐seq of nLung and GGNs, and further in vitro induced culture revealed that IL‐6 did have a promotional effect on the proliferation of NK cells, and this effect was particularly evident in GGNs 38 . The role of combined cytokine supplementation therapies based on NK cells in NSCLC has recently been demonstrated, and approaches such as NK‐92 and chimeric antigen receptor (CAR)‐transduced NK cells are being explored in lung cancer 39 .…”
Section: Lymphoid Cellsmentioning
confidence: 89%
“…CTL and NK cells are the mainstay of tumor cell killing in the adaptive and intrinsic immune systems, respectively, by the classical mechanism of the perforin‐granzyme (or granule exocytosis) pathway (Figure 1). 51 However, according to the above summary, the number and function of CD8+ T cells and NK cells are reduced in GGNs compared with nLung, 38,43 which is attributed to the fact that their function receives influence from other immune components and tumor cells. Tumor cells upregulate heterogeneous ligands such as HLA‐C molecules, and other reasons include shedding of NKG2D ligands, and release of immunosuppressive cytokines (i.e., IL‐6, IL‐10, and TGF‐β) 39 …”
Section: Interaction Between Immune Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Lung cancer is divided into various types and subtypes . Among them, adenocarcinoma, the main subtype of non-small-cell lung cancer, accounts for 50% of all lung cancer cases. , Ground-glass cells are often a precursor to lung cancer, usually adenocarcinoma of the lung . Realizing simultaneous quantification of endogenous metabolites in multiple types of lung cancer tissues can not only improve the analytical efficiency and intuitively show the distribution differences in the target analytes but also minimize the deviation in the analytical result and provide reliable information for relevant clinical research.…”
mentioning
confidence: 99%